Disparate Impacts of Performance Funding Research Incentives on Research Expenditures and State Appropriations - Xiaodan Hu; Justin C. Ortagus; Nicholas Voorhees; Kelly Rosinger; Robert Kelchen (SAGE Publishing, 2022)
Performance-based funding (PBF) policies with research incentives have grown in popularity over the years despite little understanding regarding whether they actually work. This study leverages a novel national data set to examine the impact of PBF research incentives on the research expenditures and total state appropriations among public 4-year institutions, with a particular focus on minority-serving institutions. We find that PBF research incentives had no impact on the total amount or relative share of total research expenditures or the total amount of state appropriations allocated to treated institutions, regardless of minority-serving institution status. PBF policies that allowed institutions to self-select or opt into including research incentives as part of their PBF formula had a positive impact on the relative share of expenditures allocated to research and total state appropriations.